To Fish or Not to Fish – Economic Perspectives of the Pelagic Northeast Atlantic Mackerel and Herring Fishery - Rybicki, Sandra; Hamon, Katell G.; Simons, Sarah; Temming, Axel (Frontiers in Marine Science, 2020)
Environmental, political and economic conditions influence fishermen’s decisions, which in turn have consequences on the profitability of fishing fleets. We applied the bio-economic model FishRent to understand the response of eight fleets operating in the Northeast Atlantic mackerel and North Sea autumn spawning herring fishery to a number of scenarios, including changes in recruitment, the quota allocation key, and disruptions in fish and fuel prices. In all scenarios, both the Irish and German fleets were close to the break-even point, making them more vulnerable to additional disturbances than other fleets. Yet, these events are expected to occur simultaneously and a larger margin between costs and revenue would enhance the fleets resilience. The replacement of the historical quota allocation key to countries by an allocation according to biomass distribution negatively affected the German fleet most (-450% profitable within one year from 2020 to 2021), followed by the Dutch and Danish fleets (-175% profitable on average among those fleets), while the UK and Ireland increased their profitability by more than 250%. The differences among fleets highlights the sensitivity of a historical allocation key revision. In case of a continued herring recruitment failure, the profitability of most fleets targeting herring decreased but none of the fleets had to disinvest. Declines in fish prices (16% for frozen mackerel and herring, 81% for fresh herring, and 105% for fresh mackerel on average) and increases in fuel prices (17% on average) forced the UK, Icelandic, and large-scale (>40m) Irish fleets to reduce their number of vessels by up to 40%.